Coronavirus and the law in Europe - Grochowski, Mateusz <<[VerfasserIn]>> (Intersentia, 2021)
On 30 January 2020, in response to the globalisation of COVID-19, the World Health Organization declared a Public Health Emergency of International Concern. The deadly outbreak has caused unprecedented disruption to travel and trade and is raising pressing legal questions across all disciplines, which this book attempts to address. The aims of this book are twofold. First, it is intended to serve as a 'toolbox' for domestic and European judges, who are now dealing with the interpretation of COVID-19-related legislation and administrative measures, as well as the disruption the pandemic has caused to society and fundamental rights. Second, it aims to assist businesses and citizens who wish to be informed about the implications of the virus in the existence, performance and enforcement of their contracts. Coronavirus and the Law in Europe is probably the largest academic publication on the impact of pandemics on the law. This academic endeavour is a joint, collaborative effort to structure the recent and ongoing legal developments into a coherent and pan-European overview on coronavirus and the law. It covers practically all European countries and legal disciplines and comprises contributions from more than 80 highly reputed European academics and practitioners.
Title from publisher's bibliographic system (viewed on 10 Dec 2021)